Explaining Efficiency Differences Among Large German and Austrian Banks - Hauner, David (IMF Working Papers; Working Paper ;, 2004)
Cost-efficiency, scale efficiency, and productivity change are estimated by data envelopment analysis; and cost-efficiency is regressed on explanatory variables. No evidence is found for average productivity responding to deregulation over the period studied. State-owned banks are found to be more cost-efficient (likely owing to cheaper funds) and cooperative banks to be about as cost-efficient as private banks. Increasing economies of scale but decreasing economies of scope provide rationale for M and As among banks with similar product portfolios. Interbank and capital market funding is found to be more cost-efficient than deposits when the cost of retail networks is controlled for.